The Instructional-Based Andro-Web Comics on Work and Energy Topic for Senior High School Students (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2018)
This study aimed to determine the validation of Andro-web comics on Work and Energy topic. To achieve the objective, this study was designed referring to ADDIE model, i.e, Analysis, Design, Development or Production, Implementation or Deliver, and Evaluations. The Andro-web comics could be accessed using a digital comic application, Webtoon. It is downloadable in Play store or App store. The Andro-web comics is compatible with all devices including mobile devices (phone, tablet, iPod, PDA, and smartphone) and PC/Mac. Based on the expert judgment, the Andro-web comics is suitable for learning. The Instructional-Based Andro-Web Comics is alternative instructional materials for teachers to attract students’ attention and help them studying easily and practically as it provides an interesting illustration with simple language. It could also be used wherever and whenever without teacher’s guidance. Both teachers and students could communicate on the comment column which is available in the application without time and place limitation.